Dance Entry Level Teacher Assessment (DELTA): Reframing dance teacher preparation through consensus building. Issue 3 (3rd July 2019) - Schmid, Dale
Abstract: The Dance Entry Level Teacher Assessment (DELTA) measures pedagogical content knowledge and subject-specific content knowledge in dance. Created and administered jointly by the National Dance Education Organization and the State Education Agency Directors of Arts Education, DELTA represents a first step toward reaching national consensus on the fundamental pedagogical content knowledge deemed crucial for beginning dance teachers. The vision for DELTA is that it becomes nationally recognized by state departments of education as allowable evidence of subject-matter competency to confer licensure and that it is accepted as a viable means to ensure that beginning dance teachers have the requisite skills for successful entry into the public schools. It is concomitantly intended to serve as a gateway to dance certification, a tool for programmatic evaluation, and a mechanism to codify dance teacher preparation based on a communal conceptual framework. DELTA was developed by means of a quantitative approach that connects teaching, evaluation, and educational policies. The purpose of this article is to illuminate ways in which evaluation is playing a major role in teacher preparation aligned to National Arts Standards; to support claims that DELTA is a valid indicator of teacher readiness; and provide examples of ways in which DELTA is being embraced by colleges and universities as a tool for programmatic improvement.